Answer:
8
Step-by-step explanation:
Absolute value is always the positive value of a number.
First, take a look at 3 less than twice x. Twice x would be 2x and 3 less than it would become 2x-3.
Next, 2 more than the quantity 3 times x. The quantity of 3 times x is 3x and 2 more than that would be 3x+2.
Now that we have our two equations, we need to multiply them together, which can be shown as (2x-3)(3x+2).
Then, multiply the two equations together using FOIL (multiply the first two terms, then the outside terms, then inside, and lastly, the last two terms): 2x times 3x, 2x times 2, -3x times 3x, and 2 times -3, which equates to 6x^2+4x-9x-6.
Your final answer is 6x^2-5x-6.
Answer:
Ellen invested $60 and Bob invested $140
Step-by-step explanation:
let the two amounts invested by 3x and 7x
(notice 3x : 7x = 3 : 7 )
then 3x + 7x = 200
10x = 200
x = 20
then 3x = 3(20) = 60
and 7x = 7(20) = 140
60+140=200